Predictors of progression of multiple sclerosis in a sample of Egyptian patients - Manar A. Shawky; Tarek I. Menecie; Eman M. Saif El Deen; Mohammed H. Rashad (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2024)
Abstract Background Multiple sclerosis (MS) is a multifactorial neurodegenerative autoimmune disease with a varied clinical course and presentation, which is more frequent than ever in the Middle East. The aim of this work is to investigate potential predictors of MS progression in order to help in early diagnose and predict progressive course of the disease. Results This is a retrospective case–control study conducted on a group of multiple sclerosis (MS) patients who developed secondary progression of the disease course (SPMS). The cases were matched with control MS patients who did not develop any disease progression (relapsing remitting MS (RRMS)). The matching was done for sex, and age with a ratio 1:1, total of 150 patients were included as cases and were matched with 150 control patients. Significant associations between MS progression and smoking, vitamin D deficiency, disease duration, delay in MS diagnosis, unemployment, site and number of lesions, and number of black holes were reported. About half of SPMS patients (53.3%) had 3 or more spinal lesions compared to only 1.4% of RRMS patients (p < 0.001). Moreover, about 76% of RRMS patients had no black holes in their radiological finding, while it was found that 35.3% of the SPMS patients had more than 5 black holes, compared to 8% of RRMS patients. Additionally, juxta-cortical site lesions were more frequent in SPMS than that in RRMS in a percentage 72.7 and 46%, respectively. Also, infra-tentorial lesions were found to be more frequent in SPMS group rather than RRMS group 92% and 78.7%, respectively. On the other hand, a lower SDMT scale was associated with a shorter time to SPMS diagnosis in the multivariate Cox regression analysis adjusted to baseline factors and 25-FWT (HR: 0.928, 95% CI: 0.906–0.95). Conclusions MS secondary progression can be predicted among MS patients in routine practice comprising exposure history, clinical assessment, laboratory findings, and radiological examinations.